Oral side effects of COVID-19 vaccines in 32 European countries: Analysis of EudraVigilance reports - Riad, Abanoub; Schulz-Weidner, Nelly; Dziedzic, Arkadiusz; Howaldt, Hans-Peter; Attia, Sameh; Justus Liebig University Giessen (My University, 2023)
The recent reports of oral side effects (SEs) following COVID-19 vaccination warrant further investigation into their prevalence, severity, and aetiology. This study was conducted to synthesize the first-ever population-level evidence about oral SEs of COVID-19 vaccines in Europe. The European Union Drug Regulating Authorities Pharmacovigilance (EudraVigilance) database was accessed in August 2022 to extract summary data of all potential oral SEs reported after COVID-19 vaccination. The data were reported descriptively and cross-tabulated to facilitate sub-group analysis per vaccine type, sex, and age group. Dysgeusia was the most commonly reported oral SE (0.381 case per each 100 received reports), followed by oral paraesthesia (0.315%), ageusia (0.296%), lip swelling (0.243%), dry mouth (0.215%), oral hypoaesthesia (0.210%), swollen tongue (0.207%), and taste disorder (0.173%). Females had significantly (Sig. < 0.001) a higher prevalence of all most common (top 20) oral SEs, except for salivary hypersecretion, which was equally prevalent among females and males. The present study revealed a low prevalence of oral SEs, with taste-related, other sensory and anaphylactic SEs being the most common SEs in Europe, similar to what was found earlier among the US population. Future studies should explore the potential risk factors of oral sensory and anaphylactic SEs to verify whether they are causally linked to COVID-19 vaccines.
Keywords: anaphylaxis; COVID‐19 vaccines; drug‐related side effects and adverse reactions; oral manifestations; pharmacovigilance; ddc:610